Lead-free piezoelectric composition and piezoelectric element

By using alkaline niobate perovskite oxides with optimized Mn, Ti and Sc content as the main component of the lead-free piezoelectric composition, the problem of low insulation under high temperature conditions is solved, and excellent piezoelectric characteristics under high electric field and insulation under high temperature is achieved.

CN119604478APending Publication Date: 2025-03-11NITERRA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380055965.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-09-11
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing lead-free piezoelectric compositions have low insulation under high temperature conditions, making it difficult to meet the requirements of applying high electric fields and high temperatures simultaneously.

Method used

A lead-free piezoelectric composition with alkaline niobate perovskite oxides containing Mn, Ti and Sc as the main components is used, and optimized by specific element ratios and crystal particle sizes to form excellent piezoelectric properties and high temperature insulation.

Benefits of technology

Excellent piezoelectric characteristics under high electric field and excellent insulation under high temperature conditions are achieved, solving the problem of low insulation in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604478A_ABST
    Figure CN119604478A_ABST
Patent Text Reader

Abstract

[Solution] A lead-free piezoelectric composition according to the present invention contains, as a main component, an alkali niobate perovskite oxide containing Mn, Ti, and Sc, wherein the content ratio of Sc to Ti is 0.004-8 (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lead-free piezoelectric composition and a piezoelectric element. Background Art

[0002] In the past, a large number of piezoelectric elements were made of PZT (lead zirconate titanate)-based materials. However, the lead component contained in PZT is considered to be a problem as it causes environmental load, and in recent years, the development of piezoelectric elements made of lead-free materials that do not contain lead has been promoted. As such a lead-free material, for example, alkali niobate perovskite-type oxides have been proposed.

[0003] In recent years, piezoelectric elements used in stacked actuators and the like are required to be driven by high electric fields and have high reliability. Such piezoelectric elements include a stack of piezoelectric ceramic layers formed of non-lead alkali niobate perovskite oxides and internal electrodes alternately stacked (see, for example, Patent Document 1). The piezoelectric ceramic expands and contracts according to the applied voltage, and therefore exhibits good piezoelectric properties under high electric fields.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent No. 3945536

[0007] (Problem to be solved by the invention)

[0008] Lead-free piezoelectric compositions used in conventional piezoelectric elements show good piezoelectric characteristics under high electric fields, but have a problem of low insulation properties under high temperature conditions. Summary of the invention

[0009] An object of the present invention is to provide a lead-free piezoelectric composition having excellent piezoelectric characteristics and excellent insulation properties under high temperature conditions.

[0010] (Solutions used to solve problems)

[0011] The solution for solving the above-mentioned problems is as follows.

[0012] <1> A lead-free piezoelectric composition comprising an alkali niobate perovskite-type oxide containing Mn, Ti and Sc as a main component, wherein the content ratio of Sc to Ti is 0.004 to 8.

[0013] <2> According to the aforementioned <1> In the lead-free piezoelectric composition, the alkali niobate perovskite oxide is represented by the following composition formula (1).

[0014] (A1 a M1 b ) c(Nb d1 Mn d2 Ti d3 Zr d4 Sc d5 )O 3+e ·····(1)

[0015] Among them, element A1 is at least one of Li, Na, and K, element M1 is at least one of Ba, Ca, and Sr, 0 < a < 1, 0 < b < 1, a + b = 1, 0.80 < c < 1.10, 0 < d1 < 1, 0 < d2 < 1, 0 < d3 < 1, 0 ≤ d4 < 1, 0 < d5 < 1, d1 + d2 + d3 + d4 + d5 = 1, and e is any value that can maintain the perovskite crystal structure.

[0016] <3>The lead-free piezoelectric composition according to <2> described above, wherein the foregoing element M1 contains Ba, and 0.06 ≤ b ≤ 0.20, 0.06 ≤ d4 ≤ 0.20.

[0017] <4>The lead-free piezoelectric composition according to <1> or <2> described above, wherein the average particle diameter of the crystal grains of the foregoing alkali niobate perovskite-type oxide is 1.2 μm or more and 8.1 μm or less.

[0018] <5>

[0019] A piezoelectric element having a structure in which the lead-free piezoelectric composition described in any one of <1> to <4> above and an electrode are alternately laminated.

[0020] Effects of the Invention

[0021] According to the present invention, it is possible to provide: a lead-free piezoelectric composition having excellent piezoelectric properties and excellent insulation properties under high-temperature conditions, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A perspective view of the piezoelectric element of Embodiment 1

[0023] Figure 2 A cross-sectional view of the piezoelectric element of Embodiment 2 DETAILED DESCRIPTION OF THE EMBODIMENTS

[0024] Hereinafter, the lead-free piezoelectric composition and the piezoelectric element of the embodiment will be described.

[0025] The lead-free piezoelectric composition contains an alkali niobate perovskite-type oxide containing Mn (manganese), Ti (titanium), and Sc (scandium) as a main component. That is, the lead-free piezoelectric composition has the foregoing alkali niobate perovskite-type oxide as a main phase.

[0026] The foregoing alkali niobate perovskite-type oxide is represented by the following compositional formula (1).

[0027] (A1 a M1 b ) c (Nb d1 Mn d2 Ti d3 Zr d4 Sc d5 )O 3+e ···(1)

[0028] The element A1 is at least one of Li (lithium), Na (sodium), and K (potassium) belonging to alkali metals. The element M1 is at least one of Ba (barium), Ca (calcium), and Sr (strontium) belonging to alkaline earth metals.

[0029] In the above compositional formula (1), the element A1 and the element M1 are arranged at the A site of the perovskite structure, and Nb (niobium), Mn (manganese), Ti (titanium), and Zr (zirconium) are arranged at the B site.

[0030] As the values of the coefficients a to e in the above compositional formula (1), values are selected that are preferable from the viewpoints of the electrical properties or piezoelectric properties, etc. of the lead-free piezoelectric composition among the values for which the perovskite structure is established.

[0031] Specifically, the coefficients a and b satisfy 0 < a < 1, 0 < b < 1, and a + b = 1, excluding a = 0 (i.e., a composition containing no alkali metals) and b = 0 (i.e., a composition containing neither Ba, Ca, nor Sr).

[0032] The coefficient c with respect to the entire A site satisfies 0.80 < c < 1.10, preferably 0.90 ≤ c ≤ 1.05.

[0033] The coefficients d1, d2, d3, d4, and d5 satisfy 0 < d1 < 1, 0 < d2 < 1, 0 < d3 < 1, 0 ≤ d4 < 1, 0 < d5 < 1, and d1 + d2 + d3 + d4 + d5 = 1. Excluding d1 = 0 (a composition containing no Nb), d2 = 0 (a composition containing no Mn), d3 = 0 (a composition containing no Ti), and d5 = 0 (a composition containing no Sc). The coefficient d4 of Zr can be zero (i.e., it can be a composition containing no Zr).

[0034] It should be noted that the coefficient d1 of Nb is preferably 0.745 ≤ d1 ≤ 0.950, more preferably 0.830 ≤ d1 ≤ 0.959. The coefficient d2 of Mn is preferably 0.001 ≤ d2 ≤ 0.07. The coefficient d3 of Ti is preferably 0.005 ≤ d3 ≤ 0.06. The coefficient d4 of Zr is preferably 0 ≤ d4 ≤ 0.2, more preferably 0 ≤ d4 ≤ 0.1. The coefficient d5 of Sc is preferably 0.0002 ≤ d5 ≤ 0.05.

[0035] In the coefficient 3 + e of oxygen, the coefficient e is a positive or negative value representing the deficiency or excess of oxygen relative to the coefficient of oxygen, which is usually 3. The coefficient 3 + e of oxygen can take values for the perovskite-type oxide constituting the main phase. A typical value of the coefficient e is e = 0, and preferably 0 ≤ e ≤ 0.1. It should be noted that the value of the coefficient e can be calculated from the electroneutrality condition of the composition of the main phase. Among them, as the composition of the main phase, a composition slightly deviating from the electroneutrality condition is also allowed.

[0036] In the above compositional formula (1), the aforementioned element M1 includes Ba, preferably 0.06 ≤ b ≤ 0.20 and 0.06 ≤ d4 ≤ 0.20. If the above compositional formula (1) satisfies such conditions, the piezoelectric properties (displacement properties) are particularly excellent. It should be noted that in this case, as the aforementioned conditions, it is further preferred that 0.80 ≤ a ≤ 0.94, a + b = 1, 0.80 < c < 1.10 (preferably 0.90 ≤ c ≤ 1.05), 0.745 ≤ d1 ≤ 0.885, 0.01 ≤ d2 ≤ 0.07, 0.005 ≤ d3 ≤ 0.06, 0.06 ≤ d4 ≤ 0.2, 0.001 ≤ d5 ≤ 0.04, d1 + d2 + d3 + d4 + d5 = 1, 0 ≤ e ≤ 0.1.

[0037] Among the alkali niobate perovskite-type oxides represented by the above compositional formula (1), the oxides with K, Na, and Nb as the main metal components are called "KNN" or "KNN materials", and they have excellent piezoelectric properties, electrical properties, etc.

[0038] It should be noted that the above compositional formula (1) can be rewritten by substituting as the following compositional formula (1A).

[0039] (K a1 Na a2 Li a3 Ba b1 Ca b2 Sr b3 ) c (Nb d1 Mn d2 Ti d3 Zr d4 Sc d5 )O 3+e ···(1A)

[0040] The above compositional formula (1) is equivalent to the compositional formula (1A), which is a1 + a2 + a3 = a, b1 + b2 + b3 = b. The coefficient a1 of K is 0 < a1 ≤ 0.7 (preferably 0.095 ≤ a1 ≤ 0.665), the coefficient a2 of Na is 0 < a1 ≤ 0.9 (preferably 0.285 ≤ a2 ≤ 0.855), and the coefficient a3 of Li is 0 ≤ a3 ≤ 0.2 (preferably 0 ≤ a3 ≤ 0.1). Additionally, the coefficient b1 of Ba is 0 ≤ b1 ≤ 0.05, the coefficient b2 of Ca is 0 ≤ b2 ≤ 0.05, and the coefficient b3 of Sr is 0 ≤ b3 ≤ 0.05.

[0041] In the alkali - niobate perovskite - type oxide represented by the above compositional formula (1) or compositional formula (1A), the content ratio of Sc to Ti (Sc / Ti) is 0.004 or more and 8 or less in terms of molar ratio. If the content ratio of Sc to Ti is within this range, a lead - free piezoelectric composition with excellent piezoelectric properties and excellent insulation properties under high - temperature conditions can be obtained.

[0042] In the above compositional formula (1A), preferably 0.06 ≤ b1 ≤ 0.20 and 0.06 ≤ d4 ≤ 0.20. If the above compositional formula (1A) satisfies such conditions, especially the piezoelectric properties (displacement properties) are excellent. It should be noted that in this case, as the aforementioned conditions, it is further preferred that 0.400 ≤ a1 ≤ 0.470, 0.400 ≤ a2 ≤ 0.470, 0 ≤ b2 ≤ 0.02, b3 = 0, a1 + a2 + b1 + b2 + b3 = 1, 0.80 < c < 1.10 (preferably 0.90 ≤ c ≤ 1.05), 0.745 ≤ d1 ≤ 0.885, 0.01 ≤ d2 ≤ 0.07, 0.005 ≤ d3 ≤ 0.06, 0.06 ≤ d4 ≤ 0.2, 0.001 ≤ d5 ≤ 0.04, d1 + d2 + d3 + d4 + d5 = 1, 0 ≤ e ≤ 0.1.

[0043] In the present embodiment, the proportion of the main phase contained in the lead - free piezoelectric composition is not particularly limited as long as the object of the present invention is not impaired. For example, it is preferably 50% by volume or more, more preferably 70% by volume or more, and further preferably 90% by volume or more.

[0044] The lead - free piezoelectric composition of the present embodiment may have a secondary phase formed by other crystal phases in addition to the crystal phase of the aforementioned alkali - niobate perovskite - type oxide as long as the object of the present invention is not impaired.

[0045] In addition, in the lead - free piezoelectric composition of the present embodiment, the average particle diameter of the crystal grains of the aforementioned alkali - niobate perovskite - type oxide forming the main phase is preferably 1.2 μm or more and 8.1 μm or less. If the aforementioned average particle diameter is within this range, especially the insulation properties under high - temperature conditions (such as 150 °C) are excellent. The measurement method of the aforementioned average particle diameter is as described later.

[0046] Next, refer to Figure 1 At the same time, the piezoelectric element 200 according to the first embodiment will be described. Figure 1 FIG. 2 is a perspective view of a piezoelectric element 200 according to Embodiment 1. Figure 1 As shown, the appearance is a disk, and it has: a disk-shaped piezoelectric layer (an example of a piezoelectric ceramic layer) 100, and electrodes 301 and 302 mounted on the upper surface and the lower surface of the piezoelectric layer 100. The piezoelectric layer 100 is formed of the above-mentioned lead-free piezoelectric composition. The piezoelectric layer 100 is polarized in the thickness direction. The electrodes 301 and 302 are formed of Au, for example.

[0047] Here, an example of a method for manufacturing the piezoelectric element 200 of embodiment 1 is described. First, prepare a variety of raw material powders required to form the main phase, and weigh these raw material powders in a manner to obtain the target composition. As raw material powders, oxides of each element contained in the main phase, carbonates of each element, hydroxides of each element, etc. can be used. For those formed by adding ethanol to the mixture of each weighed raw material powder, a ball mill is used, and wet mixing is preferably performed for more than 15 hours to obtain a slurry. The obtained slurry is dried, and after drying, the obtained mixed powder is pre-baked for 1 to 10 hours, for example, under an atmospheric atmosphere at a temperature of 600 to 1000° C. to obtain a powdery main phase pre-baked product.

[0048] Next, a dispersant, a binder and ethanol are added to the obtained main phase pre-baked product, and the mixture is crushed / mixed to obtain a slurry. Afterwards, the obtained slurry is dried, and the obtained dried product is suitably granulated, and the obtained product is subjected to uniaxial pressing, for example, under a pressure of 20 MPa, to obtain a disk-shaped preform. Then, the preform is subjected to CIP treatment (cold isostatic pressing treatment), for example, under a pressure of 150 MPa, thereby obtaining a molded body.

[0049] Next, the obtained molded body is kept at a temperature of 200 to 400° C. for 2 to 10 hours to perform a binder removal treatment. Then, the molded body after the binder removal treatment is kept at a temperature of 1000 to 1200° C. for 2 to 5 hours and fired in a reducing atmosphere whose pressure is controlled so that the equilibrium oxygen partial pressure of Ni / NO is on the reduction side by more than one digit, thereby obtaining a piezoelectric layer.

[0050] For example, electrodes made of Au are formed on both the front and back surfaces of the obtained piezoelectric layer by sputtering. Then, the laminated product with the electrodes formed on the piezoelectric layer is subjected to polarization treatment by applying a DC voltage of 5 kV / mm in silicone oil at 50° C., thereby realizing the voltage characteristics of the piezoelectric layer. In this way, the piezoelectric element 200 is obtained.

[0051] Next, refer to Figure 2 At the same time, the piezoelectric element 10 according to the second embodiment will be described. Figure 2 2 is a cross-sectional view of a piezoelectric element 10 according to Embodiment 2. The piezoelectric element 10 of this embodiment is as follows. Figure 2 As shown, it comprises: a piezoelectric layer (an example of a piezoelectric ceramic layer) 11; a plurality of internal electrodes 12, 13 connected to the piezoelectric layer 11; and two external electrodes 14, 15 connected to the internal electrodes 12, 13. The piezoelectric layer 11 is formed of the above-mentioned lead-free piezoelectric composition. The internal electrodes 12, 13 are mainly composed of a base metal (for example, nickel). The piezoelectric layer 11 and the internal electrodes 12, 13 are alternately stacked. More specifically, the piezoelectric layer 11 and the internal electrodes 12, 13 are stacked in the order of piezoelectric layer 11, internal electrode 12, piezoelectric layer 11, internal electrode 13, piezoelectric layer 11, etc., and one piezoelectric layer 11 is sandwiched by two internal electrodes 12, 13. The two external electrodes 14, 15 are arranged on the outer surface of the stack of the piezoelectric layer 11 and the internal electrodes 12, 13. The external electrodes 14, 15 are mainly composed of Au, for example. One end of one of the two internal electrodes 12 and 13 connected to one piezoelectric layer 11 is connected to an external electrode 14, and one end of the other internal electrode 13 is connected to another external electrode 15. By applying a voltage between the external electrodes 14 and 15, the piezoelectric layer 11 expands and contracts, and the piezoelectric element 10 as a whole expands and contracts.

[0052] Here, an example of a method for manufacturing the piezoelectric element 10 of embodiment 2 is described. First, prepare a variety of raw material powders required to form the main phase, and weigh these raw material powders in a manner to obtain the target composition. As raw material powders, oxides of each element contained in the main phase, carbonates of each element, hydroxides of each element, etc. can be used. For those formed by adding ethanol to the mixture of each weighed raw material powder, a ball mill is used, and wet mixing is preferably performed for more than 15 hours to obtain a slurry. The obtained slurry is dried, and after drying, the obtained mixed powder is pre-baked for 1 to 10 hours, for example, under an atmospheric atmosphere at a temperature of 600 to 1000° C. to obtain a powdery main phase pre-baked product.

[0053] Next, a dispersant, a binder, and an organic solvent (such as toluene) are added to the obtained pre-baked main phase, and the mixture is pulverized and mixed to obtain a slurry. Thereafter, the slurry is processed into a sheet shape using a doctor blade method or the like to produce a ceramic green sheet.

[0054] Next, an electrode layer serving as an internal electrode is formed on one side of the ceramic green sheet using a conductive paste for internal electrodes, for example, by screen printing. The electrode layer mainly contains a base metal, for example, nickel (Ni).

[0055] Then, a plurality of ceramic green sheets with electrode layers formed thereon are stacked in such a manner that the electrode layers are alternately exposed from both sides, and ceramic green sheets without electrode layers are further stacked on both the front and back sides of the obtained stacked body. The obtained stacked body is pressed to obtain a stacked body in which ceramic green sheets and electrode layers are alternately stacked. The stacked body is cut into a desired shape, and then, for example, is kept at a temperature of 200 to 400° C. for 2 to 10 hours to perform a binder removal treatment.

[0056] The binder-removed laminate is sintered at 1000 to 1200° C. for 2 to 5 hours in a reducing atmosphere whose pressure is controlled so that the equilibrium oxygen partial pressure of Ni / NO is on the reducing side by more than a single digit.

[0057] After the side of the fired laminate is appropriately ground, a pair of external electrodes formed of Au are formed on the side of the laminate, for example, by sputtering. The pair of external electrodes are formed in a manner that the laminate is placed therebetween and faces each other. The laminate formed with the external electrodes is polarized to obtain a piezoelectric element 10. In this way, a piezoelectric element (stacked piezoelectric element) 10 having a structure in which piezoelectric layers and electrodes (internal electrodes) formed of a lead-free piezoelectric composition are alternately stacked is obtained.

[0058] The manufacturing methods of the above-mentioned embodiments 1 and 2 are examples, and various other processes and processing conditions for manufacturing piezoelectric elements can be used. For example, when the lead-free piezoelectric composition includes a subphase, a variety of raw material powders required to form the subphase are prepared, and these raw material powders are used to appropriately prepare a powdered subphase prebaked product. Then, the obtained subphase prebaked product is appropriately mixed with the main phase prebaked product in a prescribed ratio to form a target piezoelectric element. In addition, as the material of the electrode, metals or alloys such as platinum (Pt), silver-palladium (Ag-Pd), and silver (Ag) can also be used.

[0059] The lead-free piezoelectric composition and piezoelectric element disclosed in this specification have excellent piezoelectric properties under high electric fields and excellent insulation properties under high temperature conditions (e.g., 150°C). Such lead-free piezoelectric compositions and piezoelectric elements can be widely used for vibration detection, pressure detection, oscillation, piezoelectric device applications, etc. For example, they can be used for sensors that detect various vibrations (such as Knox sensors and combustion pressure sensors), vibrators, actuators, piezoelectric devices such as filters, high voltage generators, micro power sources, various drive devices, position control devices, vibration suppression devices, fluid discharge devices (such as paint discharge and fuel discharge), etc.

[0060] Example

[0061] Hereinafter, the present invention will be described in further detail based on examples. It should be noted that the present invention is not limited to these examples.

[0062] [Examples 1 to 48 and Comparative Examples 1 to 8]

[0063] (Preparation of Main Phase Pre-baked Material)

[0064] As raw material powder, prepare K 2 CO 3 Powder, Na 2 CO 3 Powder, Nb 2 O 5 Powder, TiO 2 Powder, ZrO 2 Powder, MnCO 3 Powder, BaCO 3 Sc 2 O 3 Powder, these raw material powders are weighed in a manner to obtain the compositions shown in Tables 1 to 4. A suitable amount of ethanol is added to the mixture of the weighed raw material powders, and wet mixing is performed for 15 hours using a ball mill to obtain a slurry. The obtained slurry is dried, and after drying, the obtained mixed powder is pre-baked for 1 to 10 hours under an atmospheric atmosphere at a temperature of 600 to 1100° C. to obtain a powdery main phase pre-baked product.

[0065] (Fabrication of Piezoelectric Components)

[0066] The obtained main phase pre-baked product is added with a dispersant, a binder and ethanol, and the mixture is crushed / mixed to obtain a slurry. Afterwards, the obtained slurry is dried, and the obtained dried product is suitably granulated and uniaxially pressed under a pressure of 20 MPa to obtain a disk-shaped preform. Then, the preform is subjected to a CIP treatment (cold isostatic pressing treatment) under a pressure of 150 MPa to obtain a molded body.

[0067] The obtained molded body is kept at a temperature of 200 to 400° C. for 2 to 10 hours to perform a binder removal treatment. Then, the molded body after the binder removal treatment is kept at a temperature of 1000 to 1200° C. for 2 to 5 hours in a reducing atmosphere whose pressure is controlled so that the equilibrium oxygen partial pressure of Ni / NO is on the reduction side by more than one digit, and then fired to obtain a piezoelectric layer.

[0068] Electrodes made of Au were formed on both the front and back surfaces of the obtained piezoelectric layer by sputtering. Afterwards, the laminate with electrodes formed on the piezoelectric layer was subjected to polarization treatment by applying a DC voltage of 5 kV / mm in silicone oil at 50°C, thereby realizing the voltage characteristics of the piezoelectric layer and obtaining a piezoelectric element.

[0069] [Evaluation of piezoelectric characteristics]

[0070] For each piezoelectric element (piezoelectric layer) of each embodiment and each comparative example, a laser Doppler vibrometer was used to apply an electric field of 1 to 10 kV / mm, and the longitudinal displacement S of the element was measured at a measurement frequency of 100 Hz. The displacement S was divided by the electric field E to calculate the S / E value of each electric field, and the displacement characteristics (piezoelectric characteristics) were evaluated with the maximum value Smax / Emax of the S / E value. The results are shown in Tables 1 to 4.

[0071] 〔Measurement of insulation resistance〕

[0072] For each piezoelectric element of each embodiment and each comparative example, the insulation resistance (Ω·m) was measured according to the method shown below. A direct current voltage was applied for 1 minute at 5 kV / mm under the condition of 150°C silicone oil to measure the insulation resistance (Ω·m) at this time. The results are shown in Tables 1 to 4.

[0073] [Analysis of the main aspect]

[0074] For each voltage element (piezoelectric layer) of each embodiment and each comparative example, a scanning electron microscope-energy dispersive X-ray analysis (SEM-EDS) was used to perform a composition analysis of the main phase using the method shown below. The piezoelectric layer of the piezoelectric element was cut in the thickness direction, and the cut surface was polished. Then, the polished surface was photographed at a magnification of 3000 times using an SEM, and from the obtained image, three points of any crystal particles in the main phase were selected, and the crystal particles at these three points were subjected to quantitative analysis of each element using EDS. At this time, the measuring probe diameter of the electron beam was set to about 1 μm. Then, the composition of each embodiment and each comparative example was calculated based on the average value of the quantitative values ​​of each element in the crystal particles at these three points. The results are shown in Tables 1 to 4. It should be noted that the "-" in Tables 1 to 4 indicates that it is lower than the detection limit of the device.

[0075] [Average particle size of the main phase crystal particles]

[0076] The polished surfaces of the voltage elements (piezoelectric layers) of Example 12, Examples 45 to 48, and Comparative Examples 6 to 8 were photographed at a magnification of 3000 times using a scanning electron microscope (SEM). For the obtained SEM images (reflected electron images), a measurement range of a square with a side of 250 μm was set. Then, for the multiple crystal particles existing in the measurement range, the major axis diameter and the minor axis diameter were respectively calculated using image analysis software. The major axis diameter and the minor axis diameter in the crystal particles are orthogonal to each other, and the major axis diameter and the minor axis diameter are respectively set as the maximum values ​​in each axis. Then, for each crystal particle, the average value of the major axis diameter and the minor axis diameter is taken as the particle size (particle size) of each crystal particle. The average value of the particle size of each crystal particle in the above-mentioned measurement range calculated in this way is taken as the average particle size (μm) of the crystal particles of the main phase.

[0077] [Table 1]

[0078]

[0079] [Table 2]

[0080]

[0081] [Table 3]

[0082]

[0083] [Table 4]

[0084]

[0085] As shown in Tables 1 and 2, the lead-free piezoelectric composition used in the piezoelectric elements of Examples 1 to 34 contains an alkali niobate perovskite oxide containing Mn, Ti and Sc as a main component (main phase), and the content ratio of Sc to Ti in the alkali niobate perovskite oxide is 0.004 to 8 in terms of molar ratio. The insulation resistance of Examples 1 to 34 under high temperature conditions (150°C) is 4×10 8 The maximum value Smax / Emax of the S / E value in Examples 1 to 34 was 132 pm / V or more, confirming that the piezoelectric characteristics (displacement characteristics) of Examples 1 to 34 were excellent.

[0086] The lead-free piezoelectric composition of Comparative Example 1 is formed of an alkali niobate perovskite-type oxide containing Mn and Sc and not containing Ti. Although the piezoelectric element of Comparative Example 1 has excellent insulation under high temperature conditions, the maximum S / E value Smax / Emax is 98 pm / V, which has problems in piezoelectric characteristics.

[0087] The lead-free piezoelectric composition of Comparative Example 2 is formed of an alkali niobate perovskite-type oxide containing Mn and Ti and not containing Sc. The piezoelectric element of Comparative Example 2 has problems with insulation under high temperature conditions. In the case of Comparative Example 2, the insulation resistance cannot be measured. In addition, the piezoelectric element of Comparative Example 2 has problems with piezoelectric characteristics.

[0088] The lead-free piezoelectric composition of Comparative Example 3 is formed of an alkali niobate perovskite-type oxide containing Ti and Sc and not containing Mn. The lead-free piezoelectric composition of Comparative Example 3 does not contain Mn, and therefore has poor sintering properties and problems in insulation and piezoelectric properties under high temperature conditions. In the case of Comparative Example 3, the S / E value and insulation resistance could not be measured.

[0089] The lead-free piezoelectric composition of Comparative Example 4 has an excessively high content ratio of Sc to Ti (Sc / Ti=10). The piezoelectric element of Comparative Example 4 has excellent insulation under high temperature conditions, but the maximum S / E value Smax / Emax is 104 pm / V, which has problems in piezoelectric characteristics.

[0090] The lead-free piezoelectric composition of Comparative Example 5 has an excessively low content ratio of Sc to Ti (Sc / Ti=0.003). The piezoelectric element of Comparative Example 5 has excellent insulation under high temperature conditions, but the maximum S / E value Smax / Emax is 106 pm / V, which has problems in piezoelectric characteristics.

[0091] The lead-free piezoelectric composition obtains high piezoelectric properties by containing Ti, but if the content of Ti is too much, the insulation is reduced. In addition, the lead-free piezoelectric composition obtains high insulation under high temperature conditions by containing Sc. However, if a large amount of Sc is contained, it becomes easy to lose strong dielectric properties (that is, the piezoelectric properties are reduced). Therefore, when the content of Ti is small, the piezoelectric properties are reduced. It should be noted that when the content of Ti is high, it is not easy to lose strong dielectric properties. Therefore, even if a large amount of Sc is contained, the piezoelectric properties are not reduced. Therefore, it is speculated that in the case of a lead-free piezoelectric composition formed by an alkali niobate perovskite-type oxide, the content ratio of Sc relative to Ti is important for taking into account both piezoelectric properties and insulation under high temperature conditions. It should be noted that the aforementioned lead-free piezoelectric composition improves sintering properties by containing Mn, and the piezoelectric properties are reflected.

[0092] As shown in Table 3, the lead-free piezoelectric composition used in the piezoelectric elements of Examples 35 to 43 has an alkali niobate perovskite oxide containing Mn, Ti and Sc as the main component (main phase), and the content ratio of Sc to Ti in the above-mentioned alkali niobate perovskite oxide is 0.004 or more and 8 or less in terms of molar ratio. In particular, in the case of Examples 35 to 43, the alkali niobate perovskite oxide constituting the main phase of the lead-free piezoelectric composition contains Ba and Zr, and the range of the coefficient b in the above-mentioned composition formula (1) is 0.06≤b≤0.20, and the range of the coefficient d4 is 0.06≤d4≤0.20. In addition, the range of the coefficient b1 in the above-mentioned composition formula (1A) is 0.06≤b≤0.20, and the range of the coefficient d4 is 0.06≤d4≤0.20. In the case of such Examples 35 to 43, the maximum value Smax / Emax of the S / E value is 248pm / V or more, and the piezoelectric characteristics (displacement characteristics) are particularly excellent.

[0093] In contrast, as shown in Table 3, in the case of Comparative Example 6, the value of the coefficient b in the composition formula (1) for the alkali niobate perovskite oxide constituting the main phase of the lead-free piezoelectric composition is greater than that of Example 35, and the value of the coefficient d4 is greater than that of Example 35. In the case of such Comparative Example 6, the maximum value Smax / Emax of the S / E value is 91 pm / V, which has a problem in the piezoelectric characteristics (displacement characteristics).

[0094] In addition, as shown in Table 4, in the case of Example 12 and Examples 44 to 48, the average particle size of the crystal particles of the alkali niobate perovskite oxide was 1.2 μm or more and 8.1 μm or less. In the case of such Examples 12 and Examples 44 to 48, it was confirmed that the insulation properties were excellent especially under high temperature conditions (150° C.).

[0095] In contrast, as shown in Table 4, although the average particle size of the crystal particles is 4.3 μm, the content ratio of Sc to Ti in the alkali niobate perovskite type oxide is 0.003 in terms of molar ratio. In this Comparative Example 7, the insulation resistance value is low, and there is a problem in insulation. In addition, in Comparative Example 8, the average particle size of the crystal particles is too large, and in this Comparative Example 8, the insulation resistance value is low, and there is a problem in insulation.

[0096] In addition, Table 4 shows the manufacturing conditions (calcination temperature (° C.), holding time (hours)) in Example 12, Examples 44 to 48, Comparative Example 7, and Comparative Example 8.

[0097] Description of Reference Numerals

[0098] 10, 200... piezoelectric element, 11, 100... piezoelectric layer (piezoelectric ceramic layer), 12, 13... internal electrode, 14, 15... external electrode, 301, 302... electrode.

Claims

1. A lead-free piezoelectric composition, which contains an alkali niobate perovskite-type oxide containing Mn, Ti, and Sc as a main component, and the content ratio of Sc relative to Ti is 0.004 or more and 8 or less.

2. The lead-free piezoelectric composition according to claim 1, wherein: The alkali niobate perovskite-type oxide is represented by the following compositional formula (1), (A1 a M1 b ) c (Nb d1 Mn d2 Ti d3 Zr d4 Sc d5 )O 3+e ·····(1) wherein the element A1 is at least one of Li, Na, and K, the element M1 is at least one of Ba, Ca, and Sr, 0 < a < 1, 0 < b < 1, a + b = 1, 0.80 < c < 1.10, 0 < d1 < 1, 0 < d2 < 1, 0 < d3 < 1, 0 ≤ d4 < 1, 0 < d5 < 1, d1 + d2 + d3 + d4 + d5 = 1, and e is an arbitrary value capable of maintaining a perovskite-type crystal structure.

3. The lead-free piezoelectric composition according to claim 2, wherein: The element M1 contains Ba, and 0.06 ≤ b ≤ 0.20, 0.06 ≤ d4 ≤ 0.

20.

4. The lead-free piezoelectric composition according to claim 1 or claim 2, wherein: The average particle size of the crystal grains of the alkali niobate perovskite-type oxide is 1.2 μm or more and 8.1 μm or less.

5. A piezoelectric element having a structure in which the lead-free piezoelectric composition according to any one of claims 1 to 4 and an electrode are alternately laminated.

Citation Information

Patent Citations

  • Niobate base leadless piezoelectric ceramic with high tension electricity coefficient and preparation method thereof

    CN101269962A

  • Sodium columbate barium calcium zirconate titanate system leadless piezoelectric ceramic composition

    CN102515761A

  • Lead-free piezo-electric porcelain composition, piezo-electric element using the same, and method for producing lead-free piezo-electric porcelain composition

    CN104973863A

  • Lead-free piezo-electric porcelain composition, piezo-electric element using the same, and method for producing lead-free piezo-electric porcelain composition

    US20150295162A1

  • Lead-free piezoelectric ceramic composition, piezoelectric element using the same, and method of manufacturing lead-free piezoelectric ceramic composition

    US20170141293A1